(untitled) (Tempo e Argumento, 2022)
This article seeks to address the presence of Marechal Candido Rondon, character as a symbol of national integration, “father of communications” - representing the modern Brazil who wanted to introduce and teach in school enrollment. It also seeks to research to understand how the manufacturing is, first, the hero of the historical narrative, to then think about your own agent status - in its different facets and elaborations. And, finally, demonstrate the places of memory, the story written and taught about the Marechal Rondon.